Slobodan Milosevic and the destruction of Yugoslavia - Sell, Louis, 1947- (Duke backfile, 2002)
Former U.S. foreign service officer Louis Sell fills a gap in the literature on the Yugoslav conflicts by covering both the domestic Yugoslav side of the collapse and the history and consequences of international interventions in the wars in Slovenia and Croatia in 1991, Bosnia in 1992-1995, and Kosovo from 1998-1999. Sell focuses on the life and career of Milosevic, from the perspective of both a diplomatic insider intimately familiar with the region and a scholar who has researched all the available English and Serbo-Croatian sources. Sell spent much of his diplomatic career in Eastern Europe and Russia, including eight years in Yugoslavia between 1974 and 2000, and witnessed the events that contributed to the dissolution and ultimate destruction of Yugoslavia. In "Slobodan Milosevic and the destruction of Yugoslavia" he provides first-hand observations of Milosevic from the heady days of his rise to power and, later, in the endgame of the Bosnian war, including the Dayton Peace Conference. Drawing on a wide range of published material as well as interviews with Yugoslav and foreign participants, Sell covers such areas as Milosevic's relationship to the military, his responsibility for war crimes, his methods of persuasion and negotiation, and his notoriously explosive personality.